CARD SIGN MAKING SYSTEM DESIGN IN THE VILLAGE OF PAMULANG - Ai Nuraini; Drs. Sunarto Usna, MMSI (Jurnal Sistem Informasi, 2000)
Villages located Pamulang in Tangerang Regency, which is doing its job, especially taking care services to the community. Besides the task also in terms of deal-making identity cards and also provide services for citizens who want to make a marriage certificate.In conjunction with the task of all to note that the Village of Pamulang has supervisory duties towards its citizens. In order for these areas have demographic data on which these data are very important for the population census.